The association between the health-related physical fitness and inhibitory control in preschool children - Yiyan Li; Tang Zhou; Yanhua Lu; Menghao Sang; Jiajia Liu; Xiaolong He; Minghui Quan (BMC, 2022)
Abstract Background Inhibitory control develops rapidly during the preschool stage, and development of inhibitory control in this period is significant for the healthy growth of the future. However, most studies paid more attention to children and adolescents in recent years, but less focus on preschool children. Therefore, the purpose of this study was to explore the association between the health-related physical fitness and inhibitory control in preschool children. Methods This cross-sectional study was based on a baseline data from randomized controlled trial by cluster sampling(including 128 preschoolers, 70 boys, 58girls).The health-related physical fitness T-score (HPFT) was obtained by adding standard scores of six indicators: body mass index, handgrip strength, standing long jump, one-leg balance, 2 × 10 m shuttle run test, and 20 m shuttle run test. Inhibitory control was assessed using the flanker task and reflected by reaction time and accuracy. Results A total of 120 preschoolers were included in the final statistical analysis. After adjusting the confounders, HPFT was associated with reaction time (β=-2.49 ms, 95%CI: -4.22, -0.75). Similarly, a negative association was observed between one-leg balance and reaction time (β=-12.04 ms, 95%CI: -18.94, -5.15), and between 20 m shuttle run test and reaction time (β=-23.28 ms, 95%CI: -37.00, -9.56). Compared with the participants in the lowest tertile, HPFT (β=-158.74, 95%CI: -309.63, -7.84), one-leg balance (β=-267.25 ms, 95%CI: -420.71, -113.79) and 20 m shuttle run test (β=-215.58 ms, 95%CI: -374.67, -56.49) were all negatively associated with reaction time of those in the highest tertile. Conclusions Negative relationships between HPFT and RT of the inhibitory control were observed in preschoolers. To have better inhibitory control, it's suggested that HPFT of preschoolers should be at least 249. These findings are of great significance for the early improvement of HPFT and the development of inhibitory control in preschool children.